Effect of deep diaphragmatic breathing on pain in patients with metastatic gastrointestinal cancers - Rezaei, Maryam; Salari, Nader; Aznab, Mozafar; Jasmi, Sayed Vahid; Abdi, Alireza; Shohaimi, Shamarina (Elsevier, 2024)
Background: Patients with gastrointestinal cancers commonly experience acute and chronic pain. This study aimed to determine the effect of deep diaphragmatic breathing on acute and chronic pain in patients with metastatic gastrointestinal cancers. Methods: This clinical trial was conducted in Kermanshah-Iran in 2022. The sample consisted of 44 patients hospitalized in the oncology ward, who were selected by convenient sampling and randomly allocated into case and control groups. The case group performed diaphragmatic deep breathing intervention for 10 days, twice a day, for 10 min. The subjects completed pain assessment tools before and after the intervention. Data were analyzed using SPSS Version 24. Results: The study included participants with a Mean and Standard Deviation(SD) age of 53.95 ± 10.51 years. The case and control groups were similar in terms of demographic variables. The mean and sd acute pain score before the intervention was 3.50 ± 1.84 in the experimental group and 2.18 ± 1.65 in the control group (p = 0.01). However, after the intervention, the score decreased to 1.72 ± 1.07 in the experimental group and increased to 3.72 ± 1.95 in the control group (p = 0.001). The two groups did not differ significantly in terms of chronic pain before the intervention (p = 0.07). However, after the intervention, the score decreased in the experimental group and increased in the control group, with a significant difference (p = 0.01). Conclusion: The results of this study suggest that deep diaphragmatic breathing reduces pain in patients with gastrointestinal cancer. Including this method as a routine care program for cancer patients is recommended.